Comparative analysis by means of finite differences and DM methods for linearized problem of gyrotrons - Cirulis, T.; Kalis, H.; Lietuvietis, O. (Mathematical Modelling and Analysis, 2004)
The problem of Schrödinger equation with complex boundary conditions for modelling a motion of electrons in gyrotrons is considered. Numerical results obtained by using Fourier, Finite Differences (FD) and Degenerate Matrices (DM) methods are compared in the simplest case. For DM methods they are analysed also in more general cases, when FD can not be applied because of fast oscillations of the solution.Baigtinių skirtumų ir DM metodo lygiamoji analizė linearizuotam girotrono uždaviniuiSantrauka. Nagrinėjamas kraštinis uždavinys Šredingerio lygčiai, aprašantis elektronų judėjimą girotrone. Darbe lyginami ir analizuojami Furje, baigtinių skirtumų ir degeneruotų matricų (DM) metodais gauti skaitiniai rezultatai. Aptartas metodo taikymas greitų osciliacijų atvėju.First Published Online: 14 Oct 2010